2016
DOI: 10.1002/1873-3468.12224
|View full text |Cite
|
Sign up to set email alerts
|

The trigger enzyme PepA (aminopeptidase A) of Escherichia coli, a transcriptional repressor that generates positive supercoiling

Abstract: Escherichia coli aminopeptidase A (PepA) is a trigger enzyme endowed with catalytic activity and DNA-binding properties prominent in transcriptional regulation and site-specific DNA recombination. The current work demonstrates that PepA is a repressor in its own right, capable of specifically inhibiting transcription initiation at promoter P1 of the carAB operon, encoding carbamoylphosphate synthase. Furthermore, in vitro topology studies performed with DNA minicircles demonstrate that PepA binding constrains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…DNA looping may be facilitated by a DNA-bending protein such as IHF (Moitoso de Vargas, Kim and Landy 1989). DNA wrapping around hexameric PepA (aminopeptidase A, a trigger enzyme) generates a positive toroidal supercoil and represses transcription initiation at the P1 promoter of the E. coli carAB operon (Nguyen Le Minh, Nadal and Charlier 2016). Repression can also be accomplished by a TF acting as ‘anti-activator’, either by directly competing with the activator for binding to overlapping targets or by blocking the activating signal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA looping may be facilitated by a DNA-bending protein such as IHF (Moitoso de Vargas, Kim and Landy 1989). DNA wrapping around hexameric PepA (aminopeptidase A, a trigger enzyme) generates a positive toroidal supercoil and represses transcription initiation at the P1 promoter of the E. coli carAB operon (Nguyen Le Minh, Nadal and Charlier 2016). Repression can also be accomplished by a TF acting as ‘anti-activator’, either by directly competing with the activator for binding to overlapping targets or by blocking the activating signal.…”
Section: Introductionmentioning
confidence: 99%
“…PepA acts as a strong repressor of P1 activity (Charlier et al. 1995b; Nguyen Le Minh, Nadal and Charlier 2016). It is required for the PurR-mediated purine-specific repression (Devroede et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region comprises the binding sites for two transcriptional regulators, RutR and PurR, which equally interact with the P1 operator (see below). DNA topology assays indicated that wrapping of the P1 operator DNA around hexameric PepA generates a positive toroidal supercoil (Nguyen Le Minh et al 2016). In view of the ligand-independent DNA binding of PepA, its multifunctional character, and the structural deformations, PepA was originally supposed to play a merely architectural role in P1 regulation.…”
Section: Regulation Of Transcription Initiation At P1mentioning
confidence: 99%
“…In view of the ligand-independent DNA binding of PepA, its multifunctional character, and the structural deformations, PepA was originally supposed to play a merely architectural role in P1 regulation. However, recently single-round in vitro transcription assays clearly demonstrated that PepA is a repressor in its own right, and hence a trigger enzyme, that specifically inhibits transcription initiation at P1, and the associated topological change is an integral part of the regulatory process (Nguyen Le Minh et al 2016). …”
Section: Regulation Of Transcription Initiation At P1mentioning
confidence: 99%